251 Effects of Roughage Source on Rumination Time and Ruminal Ph in Steers Fed a Steam-flaked Corn Finishing Diet - Smith, Wyatt (J Anim Sci, 2021)
Research is limited on how physically effective fiber from various roughage sources aids in rumination time and ruminal pH of finishing beef cattle. This experiment’s objective was to evaluate rumination time and ruminal pH of beef steers consuming finishing diets with varying roughage sources (corn stalks, cotton burrs, or wheat silage). We hypothesized that roughage type would not impact rumination time and ruminal pH if different sources provide similar dietary neutral detergent fiber (NDF). Ruminally cannulated steers (n = 6; average BW = 644.56 + 13.15 kg) were used in a 3 × 3 replicated Latin square with 3 dietary treatments and 3, 21-d periods (20-d diet adaptation, 1-d sampling). Steers consumed a steam-flaked corn-based finishing diet containing corn stalks (CS), cotton burrs (CB), or wheat silage (WS) included at 7% (DM basis) of the diet. Dietary NDF was similar across treatments. Steers were fitted with a sensory collar to record daily rumination (Allflex Livestock Intelligence). Ruminal pH was measured using a handheld pH probe on d-21 at 0, 3, 6, 12, 24 hr postprandial. The NDF and dry matter intake (DMI) were greatest for steers consuming the WS diet (P < 0.01) while CS and CB diets did not differ (P = 0.81). While dietary NDF and estimated physically effective NDF (peNDF) were similar among roughage sources, CB had the lowest actual peNDF, consistent with lower rumination time (P < 0.01) and lower ruminal pH (P = 0.29). This experiment’s results indicate that roughage source impacted rumination time despite feeding steers a steam-flaked corn-based finishing diet with similar roughage and NDF levels. Using rumination time (min/d) to determine peNDF was a better indicator of rumen function parameters than particle size measured via the Penn State Particle Separator equation.